Determination of Cut-off Value for HER-2 Scoring based on qPCR Technique using Frozen and Archival, Formalin-fixed, Paraffin-embedded Tissues of Breast Cancer: Determination of HER-2 Scoring based on qPCR - Desriani; Budiarto, Bugi Ratno; Mirnawati, Farida; Harahap, Wirsma Arif; Hilbertina, Noza (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
This study aimed at determining cut off value for HER-2 scoring based on qPCR technique using frozen and FFPE of breast cancer tissues samples. Total numbers of samples were 23 for FFPE and 72 for frozen tissues, obtained from breast cancer patients in several hospitals in Padang, West Sumatera Province, Indonesia. Plasmid containing HER-2 gene fragment insert and Plasmid containing WHN gene fragment were prepared for standard curve. An evaluation for qPCR optimal quality was determined by CV value, coefficient of determination (R2) > 0.980, and value of efficiency percentage (% E; within the range of 90 to 105), which was then confirmed with the melt peak and agarose analysis. Determination of cut-off score was conducted with quartile calculation. The standard curve of this method showing the good performance of HER-2 scoring as shown by R2, and efficiency value of 0.9977 (98 %) and 0.9984 (97 %) for HER-2 and WHN, respectively. In addition, both the standard curves showed a slope value of -3.3 with CV value less than 10 %. On the basis of further confirmation using melt peak and agarose analysis, a single band and a single peak, especially for WHN, were proven; however, in HER-2 a small unspecific melt peak was appeared. The cuts off obtained from qPCR technique as borderline for scoring the HER-2 gene status were 2.34 to 4.79 for FFPE tissues, and were 2.61 to 4.19 for frozen samples. Thus, qPCR method may be considered as complementary technique to IHC test for confirming equivocal IHC results to improve the outcomes and healthcare diagnosis for the sub type HER-2 breast cancer patients.